Turning risk assessment and adaptation policy priorities into meaningful interventions and governance processes. (13th June 2018) - Brown, Kathryn; DiMauro, Manuela; Johns, Daniel; Holmes, Gemma; Thompson, David; Russell, Andrew; Style, David
Abstract : The UK is one of the first countries in the world to have set up a statutory system of national climate risk assessments followed by a national adaptation programme. Having this legal framework has been essential for enabling adaptation at the government level in a challenging political environment. However, using this framework to create an improvement in resilience to climate change across the country requires more than publishing a set of documents; it requires careful thought about what interventions work, how they can be enabled and what level of risk acceptability individuals, organizations and the country should be aiming for. This article is part of the theme issue 'Advances in risk assessment for climate change adaptation policy'.